1994
DOI: 10.1016/0014-5793(94)00876-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of a heterozygous mutation (Arg1174 → Gln) in the tyrosine kinase domain of the insulin receptor from a Type A insulin resistant patient

Abstract: We analysed the biochemical properties of insulin receptors of a Type A insulin resistant patient with a single heterozygous point mutation substituting Gln for Arg 1174. Insulin binding capacity and affinty to Epstein-Barr virus transformed lymphocytes was normal. Quantitative analysis of autophosphorylation and substrate phosphorylation of soluble insulin receptors isolated from patient cells revealed no differences in the basal state whereas in the presence of insulin autophosphorylation activity was only 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 50 publications
(48 reference statements)
3
17
0
Order By: Relevance
“…In agreement with a study of the Arg1174Gln mutation in patient lymphocytes transformed by Epstein-Barr virus [5], the number of insulin receptors in muscle tended to be lower (36%) in Arg1174Gln carriers compared with control subjects. Studies of CHO cells cotransfected with wild-type and mutant INSR cDNA have shown that the Arg1174Gln mutation is more susceptible to proteasomal degradation and impairs the formation of mt/wt hybrids, causing an increased fraction (∼55%) of fully functional (wt/wt) receptors at the cell surface [32].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In agreement with a study of the Arg1174Gln mutation in patient lymphocytes transformed by Epstein-Barr virus [5], the number of insulin receptors in muscle tended to be lower (36%) in Arg1174Gln carriers compared with control subjects. Studies of CHO cells cotransfected with wild-type and mutant INSR cDNA have shown that the Arg1174Gln mutation is more susceptible to proteasomal degradation and impairs the formation of mt/wt hybrids, causing an increased fraction (∼55%) of fully functional (wt/wt) receptors at the cell surface [32].…”
Section: Discussionsupporting
confidence: 88%
“…All ten family members affected by hypoglycaemia carried a heterozygous mutation in the IRTK domain of INSR (Arg1174Gln). This mutation has previously been found in three females with the type A syndrome of insulin resistance, and in an apparently healthy male [4][5][6][7]. Complete cosegregation (logarithm of the odds score 3.21) with the disease phenotype supported the proposition that the Arg1174Gln mutation was the cause of hypoglycaemia [3].…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations